The Colic leaf: an Icelandic charm and amulet - Maria Cristina Lombardi (2021)
Runic amulets have been used during the Medieval Ages all over Scandinavia in order to prevent or fight illnesses as well as discover thieves or murders and sometimes fight evil forces looming over human beings. After Chritianity had come to Scandinavia, runic amulets, very common in pagan times, continued to be carved and hung around neck or other parts of the body according to the type of negative influence one was affected by. ‘Colic leaves’ appeared in Iceland as parchment layers to be used for the same purpose. They presented texts, written in Latin alphabet, showing a mixture of pagan and Christian elements. Our paper aims at showing the dependance of this kind of pendants on runic amulet practice by analyzing the only one extant Icelandic ‘Colic leaf’, ms. Kveisublaðið Lbs. Fragm.14, preserved at the National University Library of Iceland, in Reykjavík.